Genetic analysis of short children with apparent growth hormone insensitivity - Wit, J. M. (2012)
Background/Aims: In short children, a low IGF-I and normal GH secretion may be associated with various monogenic causes, but their prevalence is unknown. We aimed at testing GH1, GHR, STAT5B, IGF1, and IGFALS in children with GH insensitivity. Subjects and Methods: Patients were divided into three groups: group 1 (height SDS <-2.5, IGF-I <-2 SDS, n = 9), group 2 (height SDS -2.5 to -1.9, IGF-I <-2 SDS, n = 6) and group 3 (height SDS <-1.9, IGF-I -2 to 0 SDS, n = 21). An IGF-I generation test was performed in 11 patients. Genomic DNA was used for direct sequencing, multiplex ligation-dependent probe amplification and whole-genome SNP array analysis. Results: Three patients in group 1 had two novel heterozygous STAT5B mutations, in two combined with novel IGFALS variants. In groups 2 and 3 the association between genetic variants and short stature was uncertain. The IGF-I generation test was not predictive for the growth response to GH treatment. Conclusion: In severely short children with IGF-I deficiency, genetic assessment is advised. Heterozygous STAT5B mutations, with or without heterozygous IGFALS defects, may be associated with GH insensitivity. In children with less severe short stature or IGF-I deficiency, functional variants are rare. Copyright © 2012 S. Karger AG, Basel.